The Influence of Celebrity Endorser and Trust on Product Purchasing Decisions Baper Shop Surabaya - Wanda Prastiti Rizki Wahyudi; Nuruni Ika Kusuma Wardhani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of celebrity endorsers and trust on purchasing decisions for Baper Shop Surabaya products. The research approach used in this research is a quantitative approach. The sample in this study consisted of 104 respondents from Surabaya city residents who were at least 17 years old and had made purchases at Baper Shop Surabaya. The sampling technique used was non-probability sampling in the form of accidental sampling. Data obtained by distributing questionnaires. The data analysis method uses Partial Least Square (PLS) analysis with the help of the SmartPLS 3.0 program. The research results show that celebrity endorsers and trust have a positive and significant effect on purchasing decisions for Baper Shop Surabaya products.